2018
DOI: 10.1016/j.bbr.2018.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of human somatosensory memory during motor learning

Abstract: Sensorimotor learning is a bidirectional process associated with concurrent neuroplastic changes in the motor and somatosensory system. While motor memory consolidation and retention have been extensively studied during skill acquisition, little is known about the formation and consolidation of somatosensory memory associated with motor learning. Using a robotic exoskeleton, we tracked markers of somatosensory and motor learning while healthy participants trained to make goal-directed wrist reaching movements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Based on these findings, action observation and passive proprioceptive training have been performed together, introducing here an additional point to discuss: The role of proprioceptive learning (or more generally, sensory learning) in the recovery process. Sensory learning is closely related to motor learning in the way in which motor learning shapes sensory networks in the brain and sensory learning changes motor areas [145,146]. In particular, sensory learning results in changes to motor networks in the brain and is also associated with plasticity in sensory systems that is determined by afferent inputs from the periphery and cortical projections from motor areas.…”
Section: Advances In Motor Control For Robotic Neurorehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings, action observation and passive proprioceptive training have been performed together, introducing here an additional point to discuss: The role of proprioceptive learning (or more generally, sensory learning) in the recovery process. Sensory learning is closely related to motor learning in the way in which motor learning shapes sensory networks in the brain and sensory learning changes motor areas [145,146]. In particular, sensory learning results in changes to motor networks in the brain and is also associated with plasticity in sensory systems that is determined by afferent inputs from the periphery and cortical projections from motor areas.…”
Section: Advances In Motor Control For Robotic Neurorehabilitationmentioning
confidence: 99%
“…In particular, sensory learning results in changes to motor networks in the brain and is also associated with plasticity in sensory systems that is determined by afferent inputs from the periphery and cortical projections from motor areas. Limited to proprioception, the idea to use robots to improve the recovery of this sensory channel has been extensively tested [145,146], in addition with supplementary vibro-tactile feedback [147].…”
Section: Advances In Motor Control For Robotic Neurorehabilitationmentioning
confidence: 99%
“…Given anatomical, functional, and physiological evidence suggesting reciprocal links between sensory and motor processes (Ostry & Gribble, 2016), consolidation of sensory memories may also play a role in motor learning. We and others have shown that motor skill learning is associated with improvements in body position sense (proprioception) that are retained at least 24 hours after practice ends (Cuppone et al, 2018;Mirdamadi & Block, 2020).…”
Section: Introductionmentioning
confidence: 85%
“…This approach has the main advantage of informing both brain regions (i.e., neuronal modules, in our case) that an event occurred in the other region, given that interaction in the brain is intrinsically bidirectional (Roelfsema and Holtmaat, 2018). For example, in the sensorimotor system, sensory simulation can help motor recovery (Cuppone et al, 2018) and motor learning can enhance sensory functions (Ostry et al, 2010;Takeuchi and Izumi, 2013). Applications of our neuroprosthetic systems to conditions where the sensorimotor interaction is impaired would allow restoration of both communication channels, suggesting improvements in current rehabilitation therapies.…”
Section: Discussionmentioning
confidence: 99%